2021
DOI: 10.1029/2020ms002353
|View full text |Cite
|
Sign up to set email alerts
|

Performance of the Taiwan Earth System Model in Simulating Climate Variability Compared With Observations and CMIP6 Model Simulations

Abstract:  Climate variability in the historical simulation of Taiwan Earth System Model version 1 (TaiESM1) is evaluated. While still subject to several common biases, TaiESM1's performance of mean climate states is among the leading CMIP6 models. TaiESM1 is capable of realistically simulating key climate features, including the diurnal rainfall, monsoon evolution, and teleconnection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 48 publications
(12 citation statements)
references
References 136 publications
0
11
0
1
Order By: Relevance
“…Then, the EOF‐modes of model data were projected onto the modes of the observed dataset to estimate the variance that the reference EOF‐modes explain in this projected dataset. The applicability of this method for model performance evaluation has been demonstrated in several studies (e.g., Wang and Dommenget, 2016; Lee et al ., 2018; Marathe et al ., 2021; Wang et al ., 2021). A brief mathematical description of this method is summarized hereunder.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Then, the EOF‐modes of model data were projected onto the modes of the observed dataset to estimate the variance that the reference EOF‐modes explain in this projected dataset. The applicability of this method for model performance evaluation has been demonstrated in several studies (e.g., Wang and Dommenget, 2016; Lee et al ., 2018; Marathe et al ., 2021; Wang et al ., 2021). A brief mathematical description of this method is summarized hereunder.…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies have discussed the CMIP model skill in simulating the observed regional and large‐scale modes of climate variability (Zhou et al ., 2009; Xavier et al ., 2010; Bayr and Dommenget, 2014; Wang et al ., 2015; Wang and Dommenget, 2016; Lee et al ., 2018; Zhou et al ., 2018; Marathe et al ., 2021; Wang et al ., 2021; Torsri et al ., 2022). Over the EA region, CMIP models have shown reasonable skill in simulating the spatial patterns of the observed modes of rainfall variability.…”
Section: Introductionmentioning
confidence: 99%
“…Taiwan's climate change research capabilities are already quite competitive at the international level. For example, the Taiwan Earth System Model (TaiESM) constructed by the Academia Sinica (Lee et al, 2020; Wang et al, 2021) ranks 8th among 37 models worldwide in terms of its comprehensive simulation and projection performance. It is comparable to the model (MRI‐ESM2.0) of the Meteorological Research Institute, Japan Meteorological Agency, and takes a leading position in Asia (Ministry of Science and Technology, 2020; Program for Climate Model Diagnosis and Intercomparison, 2022).…”
Section: Policy Implicationsmentioning
confidence: 99%
“…In order to realize a complex discrete dynamic system instead of manual calculation, we must first solve the problems in data. In recent years, the purpose of data enhancement processing can be achieved by integrating boosting algorithms in the process of complex discrete dynamic modeling [12]. e key content is to add learning skills to the system, so as to achieve accurate data analysis.…”
Section: Related Workmentioning
confidence: 99%